2013
DOI: 10.1016/j.meatsci.2013.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Longissimus thoracis, Semitendinosus and Masseter muscles and relationships with technological quality in pigs. 1. Microscopic analysis of muscles

Abstract: Three porcine muscles (Longissimus thoracis, Semitendinosus, Masseter), known to have large differences in biochemical and histological traits, were fully characterized and the link between muscle structure and quality evaluated. The oxidative Masseter had more pigment, higher content of metmyoglobin, haem iron, protein and collagen, and was redder with higher fibre numbers, fibre circularity, pH and water holding capacity than the glycolytic Longissimus. Fibre type distribution showed predominance of type IIB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 58 publications
3
33
0
Order By: Relevance
“…Ruusunen et al (2012) measured a mean proportion of total proteins in the LT between 21.8 and 22.9% and a mean proportion of dry matter ranging from 25.9 to 26.7% in various breeds in Scandinavia. Realini et al (2013) found a mean percentage of dry matter of 24.0%, and proportions of total proteins of 21.0%, collagen 0.9% and fat 2.3% in ST. The mean values found in the LT were 25.9% (dry matter), 24.4% (total proteins), 0.5% (collagen) and 1.0% (fat).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Ruusunen et al (2012) measured a mean proportion of total proteins in the LT between 21.8 and 22.9% and a mean proportion of dry matter ranging from 25.9 to 26.7% in various breeds in Scandinavia. Realini et al (2013) found a mean percentage of dry matter of 24.0%, and proportions of total proteins of 21.0%, collagen 0.9% and fat 2.3% in ST. The mean values found in the LT were 25.9% (dry matter), 24.4% (total proteins), 0.5% (collagen) and 1.0% (fat).…”
Section: Discussionmentioning
confidence: 88%
“…Tomović et al (2008) found mean a * values of 9.21 and b * of 4.68 in SM muscles 24 h post mortem with the use of a conventional method of chilling. Ruusunen et al (2012) measured mean a * values of 7.0-8.4 in LT, whereas Realini et al (2013) found an a * value of 7.53 in LT. Meat tenderness is determined by the amount and solubility of the connective tissue, shortening of sarcomeres during rigor development, post mortem proteolysis of myofibrillar and myofibrillar-associated proteins and the amount of intramuscular fat (Warner et al 2010). The pH of muscles is reduced early post mortem and it affects the shrinkage of myofibrils (Huff-Lonergan and Lonergan, 2005).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…After ingestion, carotenoids are submitted to the reactive conditions of the stomach, i.e., the presence of dioxygen, a temperature of 37°C, a pH varying between 6 and 2, constant mixing, the presence of reactive species such as oxidizable lipids and iron [27]. Indeed iron is present in foods both as heme iron (in red meat) and as the free form [31,45]. Iron could interact with carotenoids either directly by initiating their autoxidation [3,4] peroxyl radicals [1,15].…”
Section: Introductionmentioning
confidence: 99%
“…They synthesize various red, pink or yellow-orange carotenoids with original structures, which impart specific properties (e.g., solubility, stability) that differ from the more prevalent carotenoids found in fruit and vegetables. In higher plants, algae, and fungi, the carotenoids produced contain a C 40 scaffold, while bacteria can produce a diverse range of carotenoids with C 30 , C 40 , C 45 or even C 50 backbones [7]. Bacterial carotenoids bearing a short chain backbone (e.g., <C 40 ) are called apo-or diapo-carotenoids depending on whether one or both sides of the backbone have been truncated, respectively.…”
Section: Introductionmentioning
confidence: 99%